Upaya Mengembangkan Kemampuan Berhitung Melalui Permainan Tradisional Congklak Pada Anak Usia Dini Di Tk Raden Intan Gunung Pelindung - Elidatul Mawadah; Amirul Mukminin Al Anwari; Kisno Kisno; Annisa Herlida Sari (Institut Agama Islam Negeri Metro, 2022)
The ability to count is the ability that every child has to develop his abilities, his development starts from the environment closest to him. This type of research is descriptive qualitative, which takes the research location at Raden Intan Gunung Patron Kindergarten. The data sources used are primary data sources and secondary data sources. The data collection method used in this study is by using the method of observation, interviews and documentation. Data analysis techniques used are data reduction, data display and verification. And to test the validity of using source and technique triangulation. Based on the results of this study, it can be concluded that efforts to develop numeracy skills through the traditional congklak game in early childhood at Raden Intan Gunung Protector Kindergarten have been well realized. Developing numeracy skills through the traditional congklak game can make it easier for teachers to convey learning. The results of the teacher's achievements in developing numeracy skills in Raden Intan Kindergarten are that the concept of understanding children begins to be understood, early childhood numeracy begins to increase, children's mastery of concepts increases, the transition period switches from concrete to symbols. As for the supporting factors, children have enthusiasm in learning and a conducive classroom situation. The inhibiting factor is the loss of concentration in children because the class atmosphere is not conducive. Key Word: Congklak Traditional Game, Early Childhood Counting Ability